Normative values and functional fitness in 60-to-69 year-old men - Giovana Zarpellon Mazo; Tânia Bertoldo Benedetti; Sebastião Gobbi; Leandro Ferreira; Marize Amorim Lopes (Universidade Federal de Santa Catarina, 2010)
The objective of this study was to develop normative reference of functional fitness and an overall functional fitness index (OFFI) for 60- to 69-year-old men. A total of 112 older men living in Florianópolis/SC and Rio Claro/SP, who had been participating in structured and supervised physical activities on a regular basis for the past 6 months, were evaluated by the AAHPERD test battery. This battery consists of five tests that evaluate flexibility, coordination, balance and agility, muscle strength, and aerobic capacity. Percentile scores were calculated for the raw scores obtained in each test and the sum of percentiles was used as the OFFI. The 20th, 40th, 60th and 80th percentiles were taken as limits to classify the components and OFFI as very weak, weak, fair, good, and very good, respectively. The development of normative reference might be useful for professionals to improve the evaluation, supervision and prescription of physical activity to older men.